The consultant's handbook : a practical guide to delivering high-value and differentiated services in a competitive marketplace - Parikh, Samir, 1970- (Chichester, West Sussex, United Kingdom : John Wiley & Sons, Inc., 2015)
Delivers the essential practical skills needed to consult and make sharp, well prepared interactions in a wide range of business situations This comprehensive handbook covers the fundamental skills and attitudes required by successful consultants from novice to practitioner level, irrespective of their specialist area. It untangles the key variables present in any consulting service and introduces practical ways to improve their effectiveness based upon the author's experience of helping consulting organisations to develop and excel in the marketplace. The book explores consulting 'from the g.
The 50:50 RuleDelivering the Result; Optimizing the Client Experience; Chapter Summary; Chapter 7: Client Interactions and Related Obstacles; The Importance of Adaptability; Dealing with Client-Related Obstacles; Chapter Summary; Chapter 8: The Skill of Advising; The Deductive Method; The Inductive Method; Comparing the Methods; Combining the Methods; Documenting the Argument; Presenting an Argument; Chapter Summary; Index; EULA.
Includes index.
Description based on print version record and CIP data provided by publisher.
Keywords: Business consultants; Consulting firms -- Management; REFERENCE / Questions & Answers; Business consultants; Consulting firms -- Management; Business consultants; Business; Consulting firms -- Management; Electronic books